Influence of lower-limb muscle power-related variables on the ippon-seoi-nage of elite judokas - Almeida, F.; Carratala, H.; Carratala, V.; Feriche, B.; Padial, P.; Bonitch-Gongora, J. (International Journal of Performance Analysis in Sport, 2023)
This study investigated the influence of the lower-limb extension mechanical variables (strength variables) on the ippon-seoi-nage kinematic variables (technical variables) in elite judokas. Additionally, we studied the effect of performing ippon-seoi-nage with lower-limb flexion-extension action vs. without it, on the technical and strength variables, as well as on their relationship. Twenty-four male elite judokas were classified into two groups depending on the type of ippon-seoi-nage performed, i.e. with lower-limb flexion-extension action or without it. Mechanical outputs from an incremental loaded countermovement jump test were assessed, as well as kinematic variables transferred to the uke (person who is thrown) during an ippon-seoi-nage technique test. The strength parameters did not positively correlate with the technical ones, showing no transference between the variables studied. Furthermore, the judokas that performed the ippon-seoi-nage with lower-limb flexion-extension action presented lower times in the execution of the technique than the group that did not perform this action. Therefore, the transference from strength parameters to the performance of ippon-seoi-nage is not yet explained, even when considering different technical styles.